2019
DOI: 10.1177/1533033819837261
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Values of Platelet-Associated Indicators in Resectable Lung Cancers

Abstract: Background:Lung cancer is the leading cause of cancer death. Platelet-related indictors, including platelet count, plateletcrit, mean platelet volume, and platelet distribution width, not only associate with morphology and functions of platelet but also correlate with tumor development and metastasis. In the present study, we investigated the values of platelet-related indictors in the prognosis evaluation of resectable lung cancers.Methods:In total, 101 patients with resectable lung cancer were recruited in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Feng et al found that preoperative platelet count was a predictive factor for long-term survival in ESCC, especially in node-positive patients [24].Ohuchi M et al found that a high platelet count is associated with tumor progression and poor survival in patients with esophageal cancer [25]. For thrombocytosis, even in ammation-based scores, such as PLR, was established to analyzes the prognosis of maglinancies [26][27][28][29]. The reason for our nding con icted with previous studies may be that our sample size was relatively too little and the patients with relative advaned stage compared with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al found that preoperative platelet count was a predictive factor for long-term survival in ESCC, especially in node-positive patients [24].Ohuchi M et al found that a high platelet count is associated with tumor progression and poor survival in patients with esophageal cancer [25]. For thrombocytosis, even in ammation-based scores, such as PLR, was established to analyzes the prognosis of maglinancies [26][27][28][29]. The reason for our nding con icted with previous studies may be that our sample size was relatively too little and the patients with relative advaned stage compared with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy has been shown to be useful for the early detection of cancers compared to CTCs, cell‐free nucleic acids, and exosomes found at lower levels at the early stage 31,32 . Platelet‐associated indicators and platelet counts have been shown to be associated with the prognosis of resectable lung and colorectal cancers 33–35 . Moreover, Best et al 9 used NGS to examine 283 blood platelet samples isolated from healthy controls and patients with cancer and found that RNA profiles of TEPs could be used to diagnose cancer patients with 96% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets-associated indicators and platelet counts have been shown associated with the prognosis of resectable lung and colorectal cancers [37][38][39]. In addition to the predictive role of platelets-associated indicators in cancer, platelet counts, or protein markers, Best et.…”
Section: Discussionmentioning
confidence: 99%